Efektivitas Model Numbered Heads Together (NHT) Dalam Meningkatkan Kompetensi Bahasa Indonesia Siswa Sekolah Dasar: Kajian Pustaka - Sahara Annisa; Zarina Dwinta; Delva Riza; Sry Apfani (Universitas Serambi Mekkah, 2025)
This study is a literature review examining the effectiveness of the Numbered Heads Together (NHT) learning model in improving elementary school students' Indonesian language competency. The primary focus of this study is on reading and writing skills, as well as affective aspects such as student motivation and learning participation. The purpose of this study is to evaluate the extent to which the NHT model is able to encourage improved learning outcomes and the quality of the Indonesian language learning process at the elementary level. The method used is a literature review, reviewing various relevant research findings from 2020 to 2025. The results of the study indicate that the implementation of the NHT model significantly improves student learning outcomes, encourages collaboration, and builds individual responsibility within groups. Furthermore, this model has also been shown to increase student motivation and create a fun learning experience. These findings recommend the use of the NHT model as an alternative Indonesian language learning strategy in elementary schools.